Cadangan membina kompleks planetarium Majlis Hal Ehwal Agama Islam, Pusat Islam, Kuala Lumpur untuk persatuan Falak Syar'i Malaysia - 445032 Mohd. Khir @ Hamim Ahmed
The planetarium Center is an astronomical information center; a place to gain knowledge and appreciation of the wonders of the univers. It is a man-made universe shown under its dome-shaped screen, where science, art and technology work in concert. The music and the spoken word, photographic and artistic skills all meld with the beauty of the stars and planets to produce an audio visual presentation which can feed the mind, stimulate the imagination and yet relax. This project undertaken by the Malaysian Governement under its special Research Development under its special Research and Development policy, evolved in the Fifth Malaysian Plan (1986-1990). The aim of the project is to enhance the knowledge in science and technology which is applicable to the astronomical fields that will be contributed to the future generations. It also provide for the community as part of leisure activities. Thus a planetarium center is a uniquef place of entertainment and yet of learning. The site is right in the middle of Kuala Lumpur city, center. It is djacent to the city green parkland within the reach of tourist precint, linked with pedestrian path. It covers about 2.2 acres of irregular shaped land in the sloping area with the top most level reach at 60 feet high. The site is located toone major road with a traffic dispersal system that needs a very careful study to solve the traffic flow and pesestrian pattern to get an adequate access to the site.The design intention is to be explored in accordance to the client interests; that the design should anticipate time in the future to inspire younger generations to absorb the knowledges in science and technology which has to be exphasized throughout numerous architectural aspects within today's technology possibilities. To learn and create a design which needs a speciallise in understanding the criteria and all aspect of technical requirements and concepts, especially to clarify the specification of equipments from manufacture's detail. "Science and Technology" are two words become a major issues in the design policies to be carried -out all the way during the design process which create another design theme: "The belief that technological 'know-how' is a part and parcel of the language in architecture". Apart from this, planning concepts is based on astronomical's theory; "A Big Bang Theory" to explain the dispersive and explosive motion in an early process of heavely star exist in the universe, that is to be articulated in the hierachy of spaces. In the planetarium theatre, the show at certain extents can bring the audience a real close-up view to the outer space. So, architectural concepts is interpreted to get a real impression from the metaphor of space craft into the whole architectural forms, spaces and visual images.